2021
DOI: 10.1177/08980101211039086
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Psilocybin-Assisted Psychotherapy to Support Patients With Cancer: A Critical Scoping Review of the Research

Abstract: Treatments for addressing psychiatric mental health issues in vulnerable patients with cancer are established. Yet, many patients persist with unrelenting psychological difficulties despite intervention. There is growing interest in the role of psilocybin-assisted psychotherapy for managing treatment-resistant mental health challenges in patients with cancer. Psilocybin is a naturally occurring compound derived from certain mushroom species that can induce entheogenic experiences or an altered state of conscio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(85 reference statements)
1
3
0
2
Order By: Relevance
“…Predominaram produções de abordagem quantitativa e decorrentes de ensaios randomizados controlados. Todos os materiais selecionados apontam para a eficácia da psilocibina em reduzir os níveis sintomáticos de depressão e ansiedade em portadores de câncer com risco à vida, bem como em gerar benefícios que ajudam direta ou indiretamente no enfrentamento da doença (Moreno et al, 1999;Ross et al, 2016;Ross et al, 2021;Yu et al, 2021;Lehto et al, 2022).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Predominaram produções de abordagem quantitativa e decorrentes de ensaios randomizados controlados. Todos os materiais selecionados apontam para a eficácia da psilocibina em reduzir os níveis sintomáticos de depressão e ansiedade em portadores de câncer com risco à vida, bem como em gerar benefícios que ajudam direta ou indiretamente no enfrentamento da doença (Moreno et al, 1999;Ross et al, 2016;Ross et al, 2021;Yu et al, 2021;Lehto et al, 2022).…”
Section: Resultsunclassified
“…Além disso, demonstram que a substância não apenas foi capaz de melhorar a qualidade de vida desta população estudada, mas também fazer isso de maneira rápida e sustentada, o que representa uma grande vantagem em relação aos fármacos tradicionais. Na seção seguinte, tais achados serão discutidos com base nos referenciais que nortearam esse estudo (Ross et al, 2016;Ross et al, 2021;Yu et al, 2021;Lehto et al, 2022).…”
Section: Resultsunclassified
“…Participants attributed these effects squarely to the treatment experience (Griffiths et al 2016). Finally, in a 2021 review of eight studies of psilocybin in PLWC (four quantitative, two mixed-method, and two qualitative), the majority of patient experiences were summarized as positive, centering on themes of death acceptance, reflection, and broadened spirituality (Lehto et al 2022). While more work remains to be done in this nascent area, it appears very promising as a way to accelerate or supplement the therapeutic process of meaning making with the aid of psychoactive substances.…”
Section: Psychedelic Therapiesmentioning
confidence: 99%
“…Lehto et al, in a critical scoping review, evaluated PAT in participants with cancer. 15 These authors systematically identified all assessments used, including spirituality measures, but did not provide detailed discussion of conceptual elements of the measures. 15 To address current gaps in the PAT literature, the purpose of the current review is to evaluate experimental studies of psilocybin that assess spirituality in participants with serious illness.…”
Section: Introductionmentioning
confidence: 99%
“…15 These authors systematically identified all assessments used, including spirituality measures, but did not provide detailed discussion of conceptual elements of the measures. 15 To address current gaps in the PAT literature, the purpose of the current review is to evaluate experimental studies of psilocybin that assess spirituality in participants with serious illness. The findings from this review will provide context on how spirituality, mysticism, and related constructs are measured - an important consideration as PAT continues to show safety and efficacy for existential anxiety, depression, and demoralization in serious illness.…”
Section: Introductionmentioning
confidence: 99%